Quantitative elemental localisation in plants using ion beam microprobe analysis - Szikszai, Zita (Acta Biologica Szegediensis, 2008)
In plant biology there are efforts to study the accurate elemental concentrations and localisations in plant tissues on a microscopic scale. Ion beam analysis successfully introduced into material science, geology, archaeology and aerosol study offers a good possibility to carry out quantitative elemental investigations in plant samples. In this work we show the applicability of ion beam analysis at the microprobe facility available in ATOMKI, Debrecen, in plant studies. Concentrations and distributions of major, micro- and trace elements were determined within the roots of Bidens tripartitus. Metals were found in higher concentrations in the rhisodermis than in the inner tissues. Besides concentration values maps of elemental distribution in the tissues are also presented. Ion beam microprobe analysis can successfully complement bulk techniques in studying the uptake and transport processes of various elements in plants.